Review Prototipe Pendingin Mesin Kecil Berbasis Teknologi Peltier - Agil Hidayatulloh; Dan Mugisidi (Prosiding Seminar Nasional Teknoka, 2025)
Peltier technology uses the thermoelectric effect to transfer heat from one part of the module to another, allowing it to function as a cooler or heater without moving mechanical components. Despite its advantages in terms of reliability and environmental compatibility, Peltier modules still lack energy efficiency compared to traditional cooling systems. Previous research has focused on improving performance through innovations in semiconductor materials, thermal system design, and optimization techniques. In applications to small machines, key challenges include managing the heat on the hot side, incorporating compact designs, and maintaining stable operating temperatures. However, research findings indicate that with appropriate design and material advancements, Peltier modules have the potential to provide efficient and sustainable cooling solutions for low-power machines and portable biomedical devices.